Natural Environment Teaching for Functional Communication in Children with Speech Delay - Tri Gunadi (Yayasan Cerdas Pedia Indonesia, 2026)
This study evaluates the efficacy of Natural Environment Teaching (NET) in enhancing functional communication for children with speech delay. Utilizing a rigorous ABAB single-subject experimental design, the investigation focused on a four-year-old male diagnosed with Language Disorder. Results demonstrated a clinically significant elevation in Functional Communication Responses (FCR), with mean frequencies escalating from 2.4 at baseline to 11.4 during the final intervention phase. Visual analysis confirmed a robust functional relationship, supported by 0% data overlap and Non-Overlap of All Pairs (NAP) values between 0.96 and 1.00. Furthermore, the participant exhibited a systematic reduction in prompt dependency and successful generalization of communicative gains to domestic settings and unfamiliar partners. Concomitant decreases in maladaptive behaviors suggest that NET effectively replaces non-verbal topographies with functional verbal repertoires. These findings strongly validate NET as a scalable, ecologically valid intervention model particularly suited for the Indonesian clinical landscape where specialized therapeutic resources remain highly limited.